OCCUPATIONAL RISK MANAGEMENT FOR THE CODING OFFICER OF THE MEDICAL RECORD INSTALLATION SECTION OF BANTEN REGIONAL PUBLIC HOSPITAL - Zia'ul Fatwa Andini Yusuf; Eva Muti'ah; Basrowi Basrowi (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2023)
The hospital is a health service facility that is needed by all levels of society in an effort to improve the health status of both individuals and society. To meet these needs, hospitals are required to provide the best and quality services. Occupational safety and health is an important factor for creating labor productivity, especially in this globalization era. One of the important services of the hospital is the medical record installation service which serves the filing of documents regarding identity, examination, treatment, actions and services for patients and coding of disease diagnoses. This study aims to find out the working description of coding officers at Banten Hospital, analysis of work risks that occur in coding officers and their risk management. The research method used a qualitative descriptive which was conducted from March 2022-April 2022 on coding officers at the medical record installation at the Banten Regional General Hospital. The research was conducted using in-depth interview techniques with 2 coding officers regarding everything needed in the research. The results of the study showed that there were 6 risks at work for coding officers at Banten Hospital which were divided into 3, namely mild, moderate, and severe risks. The solution that can be done is to make SOPs regarding work safety for coding officers at Banten Hospital so that a fit body is created so that they can work optimally